THREE CENTURIES OF BIOLOGY IN ST. PETERSBURG - S. V. Shalimov (Вавиловский журнал генетики и селекции)
The paper is dedicated to the fundamental book «Biology in St. Petersburg. 1703–2008». The reviewer underlines the main advantages of the book and makes some remarks and wishes. The conclusion about a notable role of the new publication for further studies in the history of biology is made.